Alexander Lernet-Holenia und Maria Charlotte Sweceny - Dietz, Christopher (2013)
In the centre of this study stand some 154 letters exchanged between the Austrian writer Alexander Lernet-Holenia (1897-1976) and Maria Charlotte ("Lotte") Sweceny (née Stein, 1904-1956), the co-proprietor of the Viennese publishing house Manz, between 1938 and 1945. The transcripts are followed by a commentary that aims to elucidate the historical, individual and geographical references. A methodological note explains the corpus' provenance and method of transcribing and commenting on the letters adopted in the thesis. The last chapter of this study is devoted to Lotte Sweceny, the letters' addressee, and her family background. The letters' existence is due to the fact that the couple was separated by the outbreak of WW II and continued their relationship through correspondence. In September 1939 Lernet took part in the "Wehrmacht's" raid on Poland and was lightly wounded. As a result he spent the rest of the war on a leave of absence in his house in St. Wolfgang and, after September 1941, in Berlin. There, he worked as head of development of the "Heeresfilmstelle" (an office in charge of producing NS propaganda films), writing scripts himself and evaluating those by others. In these years, two of his most important novels, Mars im Widder (Mars in Aries) and Beide Sizilien (The Two Sicilies), were written - both are today considered as running counter to NS propaganda. Lotte Sweceny and her friends found their way into the set of characters and into the plot of Mars in Aries. The collection of poems Die Trophae (The Trophy) also originated from these years. When published in 1946, Lernet dedicated this work - which he considered to be his best - to Lotte Sweceny. The letters contain important background and numerous insights about the genesis and subsequent publicati ...